INTRODUCTION POPULATIONS OF USEFUL PLANTS IN THE YAKUT BOTANICAL GARDEN - Varvara V. Semenova; Nadezhda S. Danilova (Юг России: экология, развитие)
Aim. The aim is to study the ontogeny and structure of introduced populations of useful plants in Central Yakutia. Methods. Description of the ontogeny of the plants under study was carried out with the determination of ontogenetic states according to generally accepted methods. After planting, current measures were taken to care for plants with elimination of weeds and preservation of the undergrowth. The number of plants at the planting sites was calculated annually. Results. In plants, there is a polyvariety of the rate of development, in which the life cycle is shortened in individuals, the rate of development is accelerated or the ontogenetic states are missed, and there is also transition of plants to a temporarily non-flowering state. All studied introductory populations were left-sided and had different absolute maxima, which depended on the life form and duration of plant stay in culture. Conclusions. Among young monocentric plants we saw the development and attenuation of the population (Delphinium grandiflorum, Linum komarovii, Plantago major, Redowskia sophiifolia). In them, absolute maximums fall on juvenile, immitric, virginile and young generative groups. In populations of monocentric perennial plants, Lilium pensylvanicum and Adonis sibirica, absolute maxima fall on virginile groups. For studied years, the nature of the developmental spectrum in populations of Clausia aprica and Tussilago farfara has not changed with the absolute maximum in the virginal group.